2000
DOI: 10.1002/1099-1409(200008)4:5<510::aid-jpp278>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniformly substituted phthalocyanines and related compounds: alkylated tribenzo-imidazolo[4,5]- porphyrazines

Abstract: The synthesis and properties of ‘3:1’ phthalocyanines, in which three of the benzenoid rings are similarly substituted whereas the fourth is differently substituted or is replaced by a heteroaromatic ring, are overviewed with an emphasis on contributions from the group at the University of East Anglia. The synthesis of novel hepta-alkylated tribenzo-imidazolo[4,5]porphyrazines as metal-free derivatives by cross-condensation of 3,6-dialkylphthalonitrile and 1-alkyl-4,5-dicyanoimidazole is described. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…However, on further heating to 220 8C there is an irreversible change arising from an oligomerisation process, which presumably occurs through the diyne unit in the annulene ring. A minor product of the oxidative coupling of the diethynylphthalocyanine has been identified as the cyclic trimer, a triphthalocyaninodehydro [18]annulene. Compared with the diphthalocyaninodehydro [12]annulene, the compound shows a less strongly split Q-band, and the chemical shifts of protons in proximity to the annulene ring are deshielded.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, on further heating to 220 8C there is an irreversible change arising from an oligomerisation process, which presumably occurs through the diyne unit in the annulene ring. A minor product of the oxidative coupling of the diethynylphthalocyanine has been identified as the cyclic trimer, a triphthalocyaninodehydro [18]annulene. Compared with the diphthalocyaninodehydro [12]annulene, the compound shows a less strongly split Q-band, and the chemical shifts of protons in proximity to the annulene ring are deshielded.…”
Section: Resultsmentioning
confidence: 99%
“…The crude product was purified by column chromatography over silica (eluent: petrol/CH 2 Cl 2 2:1) and recrystallised from cyclohexane to afford compound 8 (1.43 g, 43 % 75.75,70.40,31.81,30.57,18.70,18.66,13.07,12.98;MS (70 eV,EI): m/z (%): 350.1 (4.8), 352.1 (4.5) [M] ; IR (nujol): n Ä 2230 cm À1 (m); elemental analysis calcd (%) for C 16 H 19 N 2 O 2 Br 1 (351.24): C 54.85,H 5.47,N 8.00,Br 22.54;found C 54.71,H 5.43,N 7.89,Br 22.67. 1,11,15,18,22,phthalocyaninato nickel(ii) (3): Freshly cleaned lithium (ca. 50 mg, 7.5 mmol) was added to 3,6-didecylphthalonitrile [21] (2.56 g, 6.27 mmol) and 7 (0.30 g, 0.70 mmol) in refluxing butanol (20 mL) under argon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] It was reported that only its Nalkylated derivatives can react in mixed co-condensation with substituted phthalodinitriles affording low symmetry (N-alkylimidazo)tribenzoporphyrazines. [11] In present work we have made an attempt to obtain imidazo annulated porphyrazine [ Experimental UV-vis spectra were recorded using Hitachi U-2000 spectrophotometer. MALDI-TOF spectra were measured on Ultraflex Brucker Daltonics mass-spectrometer without matrix or with CCA matrix.…”
Section: Introductionmentioning
confidence: 99%